Undercooling measurement and nucleation study of silicon droplet solidification. Issue 1 (23rd September 2014) - Tsoutsouva, M.G.; Duffar, T.; Garnier, C.; Fournier, G.
<x xml:space="preserve">Abstract</x> An experimental setup has been designed and developed for the study of nucleation phenomena, where a silicon droplet is directly placed, melted and solidified on a substrate. The melting‐solidification process was filmed and the undercooling temperature was measured by monochromatic and bichromatic pyrometers. It was found that the nature of the material of the substrate plays a role on the solidification process and droplet formation. The figure illustrates the macroscopic top/side views of solidified silicon droplets on fused silica and zyarock substrates. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>